CIA target the USSR - "Yakovlev, Nikolai" (Moscow, 1984)
This book covers about CIA targets. This book covers the following topics The war after the war; From the OSS to the CIA; The gentleman's club and the academic community; The CIA in psychological warfare; The summing-up:old merchandise in a New wrapping etc.
Keywords: Intelligence service - United States